Development of Methods for the Synthesis of Malathion-D6, Chlorophos-D6, and Dichlorophos-D6 for Use as Internal Standards in the Analysis of Medicinal Plant Raw Materials and Herbal Medicinal Products - V. I. Krylov; V. A. Yashkir; A. V. Braun; I. I. Krylov; O. V. Fateenkova; A. M. Savvateev (Регуляторные исследования и экспертиза лекарственных средств, 2023)
Scientific relevance. Deuterated analogues of test substances, when used as internal standards, enable analysts to determine traces of residual pesticides in a medicinal plant raw material by gas or liquid chromatography coupled with mass spectrometry. This prompts the search for an undemanding method for the synthesis of deuterated reference standards, with the ultimate goal of expanding the range of reference standards produced in Russia.Aim. The study aimed to synthesise deuterated reference standards (malathion-D6, chlorophos-D6, dichlorophos-D6, and their precursors) and determine their spectral characteristics using 1Н, 2Н, 13С and 31Р nuclear magnetic resonance (NMR) spectroscopy and high-resolution mass spectrometry.Materials and methods. The study involved methanol-D4, phosphorus pentasulfide, phosphorus trichloride, maleic acid diethyl ether, triethylamine, hydroquinone, and chloral hydrate. The authors recorded 1H, 2H, 13C, and 31P NMR spectra using a QONE AS400 NMR spectrometer operating at a temperature of 298 °K and respective frequencies of 399.83, 61.38, 100.55, and 161.85  MHz. Mass spectra were obtained using an analytical system comprising an Agilent Infinity 1260 liquid chromatograph equipped with an automatic sample injector and coupled with a Thermo Scientific Orbitrap Fusion Lumos high-resolution mass-selective tandem spectrometer operating in electrospray ionisation mode.Results. The authors used existing methods for the synthesis of organophosphate pesticides as a basis and developed synthesis routes to produce the deuterated analogues malathion-D6, chlorophos-D6, and dichlorophos-D6. The synthesised compounds were identified by NMR spectroscopy and high-resolution mass spectrometry.Conclusions. The synthesised compounds are highly pure and suitable for use as internal standards in the determination of organophosphate pesticides in medicinal plant raw materials. The synthesis methods developed by the authors can be used to produce reference standards in Russia.